2015
DOI: 10.15517/aie.v15i2.18955
|View full text |Cite
|
Sign up to set email alerts
|

Flexibilidad curricular en la implementación de proyectos de investigación para mejorar el aprendizaje de los estudiantes. El caso de Nepso Chile

Abstract: Los contenidos de este artículo están bajo una licencia Creative Commons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
1
0
2
Order By: Relevance
“…Villaça and Brito (2016) point out that through working with Nepso, students and teachers mobilize concepts and procedures of school mathematics more intimately and they appropriate numeracy and literacy practices, expanding their possibilities of reading of the world. Williamson and Hidalgo (2015), within the scope of the Polo Chile, concluded that Nepso responds to some of the current needs to improve the quality of learning and pedagogical practices, thereby, contributing to resolving that country's public education crisis. Williamson et al (2011) implied that practicing this methodology, students and teachers of the youth and adult education experience significant democratic processes in the production of knowledges in which they themselves feel the authors and generators of their own learning.…”
Section: Nepso and The Opinion Educative Surveymentioning
confidence: 99%
“…Villaça and Brito (2016) point out that through working with Nepso, students and teachers mobilize concepts and procedures of school mathematics more intimately and they appropriate numeracy and literacy practices, expanding their possibilities of reading of the world. Williamson and Hidalgo (2015), within the scope of the Polo Chile, concluded that Nepso responds to some of the current needs to improve the quality of learning and pedagogical practices, thereby, contributing to resolving that country's public education crisis. Williamson et al (2011) implied that practicing this methodology, students and teachers of the youth and adult education experience significant democratic processes in the production of knowledges in which they themselves feel the authors and generators of their own learning.…”
Section: Nepso and The Opinion Educative Surveymentioning
confidence: 99%
“…La investigación en sala de clases es una potente didáctica "intercultural", por sus objetivos de aprendizaje ciudadano, de conocimiento de la comunidad local, de generar conocimiento compartido entre profesores/as, educadores/as, estudiantes, para aprender la lengua y cultura, investigando el territorio (Williamson, 2019). Es un instrumento pedagógico que coloca a los estudiantes como protagonistas del descubrimiento, producción y sistematización de conocimientos articulados entre los formales escolares y los formales comunitarios (interculturalidad, intertransdisciplinariedad, integración curricular) con el apoyo de sus maestros/as (Williamson e Hidalgo, 2015). Los educadores y educadoras que trabajan con la diversidad cultural y lingüística de sus estudiantes deben asumir el papel de un docente o investigador (Jakku-Shivonen, y Niemi, 2011) para que puedan desempeñarse como formadores reflexivos, críticos y productores de conocimiento (Becker y Marques, 2007) junto a los estudiantes en un proceso cooperativo de interrelaciones culturales.…”
Section: Asignatura Lengua Indígena (Ali)unclassified
“…Coloca a los docentes como investigadores, junto a los estudiantes, en un proceso de descubrimiento auténtico de la realidad del territorio en que viven (Stecanela y Williamson, 2013). El proyecto se ha desarrollado desde el año 2006 a la fecha, en escuelas básicas desde el 5° año de educación básica, liceos de enseñanza media y centros de educación de personas jóvenes y adultas (EPJA), en distintas regiones, con varias y diversas modalidades de instalación en los procesos curriculares (Williamson e Hidalgo, 2015).…”
Section: La Investigación Como Un Método Pedagógico Críticounclassified